Information systems engineering in complex environments : CAiSE Forum 2014, Thessaloniki, Greece, June 16-20, 2014, selected extended papers /: CAiSE Forum 2014, Thessaloniki, Greece, June 16-20, 2014, selected extended papers. (2015) - Unknown
No abstract available